2014
DOI: 10.4274/tnd.24471
|View full text |Cite
|
Sign up to set email alerts
|

Multipl Skleroz Hastalarinda Umutsuzluk, Depresyon Ve Yaşam Doyumu

Abstract: Objective: This study was carried out to determine the level of hopelessness, depression, and life satisfaction among patients with multiple sclerosis. Ma te ri al and Met hod:Sixty-five patients with multiple sclerosis, treated at the neurology clinic of a university hospital, were included in this study. In this descriptive study, a data collection form developed by the researchers, the Beck Depression Scale, and the Beck Hopelessness and Life Satisfaction Scale were used.Re sults: Almost half (43.1%) of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
(45 reference statements)
1
2
1
Order By: Relevance
“…However, this study’s results appeared significantly lower than the results of Babamohamadi et al's (2016) study, which may be attributed to the lower mean age and shorter duration of MS in this study. Aşiret et al (2014) also observed that women had a significantly lower level of life satisfaction than men; however, this was not confirmed in this study nor in a study by Lucas-Carrasco et al (2014). Moreover, it has also been shown that the longer the duration of disease, the level of life satisfaction (SWLS) is decreased ( p = .007).…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…However, this study’s results appeared significantly lower than the results of Babamohamadi et al's (2016) study, which may be attributed to the lower mean age and shorter duration of MS in this study. Aşiret et al (2014) also observed that women had a significantly lower level of life satisfaction than men; however, this was not confirmed in this study nor in a study by Lucas-Carrasco et al (2014). Moreover, it has also been shown that the longer the duration of disease, the level of life satisfaction (SWLS) is decreased ( p = .007).…”
Section: Discussioncontrasting
confidence: 87%
“…The mean SWLS score was 15.95 ± 6.27, which corresponds with results obtained by Aşiret et al (2014) and Lucas-Carrasco et al (2014). However, this study’s results appeared significantly lower than the results of Babamohamadi et al's (2016) study, which may be attributed to the lower mean age and shorter duration of MS in this study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The later can also be influenced by culture (Eklund, 2004; Eklund & Gunnarsson, 2008; Manee et al, 2015). Moreover, people with MS need to cope with their changing health and adapt to life-changing circumstances (Aşiret, Özdemir, & Maraşlıoğlu, 2014; Ozdemir & Duru Aşiret, 2011). Adolph Meyer, cited by Yerxa (1998), claimed that satisfaction is “doing and getting enough” and is one of the most important aspects of everyday life for occupational therapists to focus on.…”
Section: Introductionmentioning
confidence: 99%